Value of diffusion MR imaging in differentiation of recurrent head and neck malignancies from post treatment changes. (September 2019) - Jajodia, Ankush; Aggarwal, Deepa; Chaturvedi, Arvind K.; Rao, Avinash; Mahawar, Vivek; Gairola, Munish; Agarwal, Mudit; Goyal, Sumit; Koyyala, Venkata Pradeep Babu; Pasricha, Sunil; Tripathi, Rupal
Highlights: Recurrent lesions have significantly lower ADC value than that of post treatment changes. ADC has 96% sensitivity, 83.3% specificity, 96% positive predictive value, 83.3% negative predictive value and 96.6% accuracy in differentiating residual/recurrent disease from post treatment changes. Positive & negative predictive value, sensitivity, specificity of differentiating tumor recurrence from post treatment changes with PET-CT was 90.6%, 100%, 100% and 40%. Abstract: Purpose: Role of diffusion-weighted (DW) MR imaging in differentiating residual or recurrent neck malignancies from postoperative/post-radiation changes with histopathological correlation and comparison with PET-CT. Methods and materials: Prospective observational study for a period of 1 year in 62 post-radiation/post-operative patients suspected to have residual/recurrent tumors of neck with lesion diameter more than 5 mm measured on MRI. Results: Mean ADC for recurrent/residual tumors: 1.008 ± 0.220 × 10 −3 mm 2 /s - significantly lower than mean ADC value for post-treatment changes of 1.69 ± 0.40 × 10 −3 mm 2 /s (p < 0.0001). The overall diagnostic accuracy, positive predictive value (PPV) and negative predictive value (NPV) of the qualitative assessment for the use of DWI in differentiating tumors recurrence from post-treatment changes were 96.6%, 96% and 83.3%, respectively. Upon quantitative analysis of the DW imaging data, a threshold ADC value of 1.3 × 10 −3 mm 2 /s used for differentiating between post-treatment changes and recurrent cancers showed the highest combined sensitivity of 94%, specificity of 83.3%, accuracy of 93.6%, positive predictive value of 95.9%, and negative predictive value of 83.3%. Conclusion: DW MRI is a promising non-invasive MRI technique used to differentiate recurrent/residual head and neck malignancies from posttreatment changes based on ADC values. DWI offers advantage as it has a short scanning time and can be safely added to standard MRI protocol with minimum patient discomfort. Complementary use of DWI and PET/CT imaging may increase diagnostic confidence for differentiating recurrent disease from radiation therapy-induced changes after 6–12 months in posttreatment cases.